Water/oil flowing imaging of electrical capacitance tomography system - 450297 Tan, Ching Tat (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical Engineering (Electrical)) - Universiti Teknologi Malaysia, 2003